Perancangan User Experience Aplikasi Pembelajaran Pembuatan Konten Digital dengan menggunakan Human Centered Design - Alfi Musyaffa Ghossa; Hanifah Muslimah Az-Zahra; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Small and Medium Enterprises (SME) are individual businesses in terms of business that refer to productive economic efforts following the statutory benchmarks described in Law No. 20 of 2008. The occurrence of the COVID-19 pandemic has hampered the movement of SMEs in several ways such as production and marketing. But in the current modern era, the development of existing technology can be utilized as best as possible, of course by SMEs who are in difficult times. The intended use of technology is the use of online buying and selling media such as e-commerce or social media that can reach a large area and have minimal mobility. There is content needed in doing marketing digitally, one of which is images and videos. For this reason, training is needed for MSMEs to be able to create content that sells their products, especially for SMEs who do not have experience in the world of digital marketing. Design (HCD), which is the process of reimagining a product or service by prioritizing the needs of users. It is also a design philosophy by revealing user needs, behavior, characters, pain points, motivation through ethnographic research to get a better user experience design. The process of extracting data conducted in this study is by conducting interviews of concerned sources (SMEs), then continuing to design the context specifications of use and specifications of user needs. After that was made a solution design that is UX design in the form of the low-fidelity prototype in the form of a wireframe, which then conducted a wireframe usability evaluation of five application user representations (SMEs). From the results of the implementation and improvement of the low-fidelity prototype, a high-fidelity prototype was obtained. These results are then evaluated by three expert evaluators using heuristic evaluation methods. At this evaluation stage found six findings of problems that had an average severity rating with minor categories. Then seven problem findings have a severity rating with a medium category. Then four problem findings have an average severity rating with major categories. The findings of the usability problem then made improvements by the advice given by the evaluator, so that the results can be accepted by the user later.